Penanganan Anak Berkelainan Penyandang Autis Melalui Komunikasi Orang Tua Sebagai Kunci Keberhasilan - Agus Prasetya; Ratna Pangastuti; Ani Anjarwati (JECED : Journal of Early Childhood Education and Development, 2022)
Degenerative disease in general has always been a political problem related to how to deal with it and the state is present. This political issue is related to problems and procedures from the very beginning, where from the time of diagnosis of a disease to how to determine the future of people with disabilities or disabilities in the future. Since the parents received an expert diagnosis that their child was suffering from an autistic disease, since then life has changed. The illness suffered by a person after undergoing the process of being diagnosed by an expert will sooner or later affect the dynamics that affect all those affected towards their lives and themselves. Autism, a behavioral disorder that occurs when children are growing and developing, will affect families and family resources, especially when children grow and develop towards school age. This study wants to explore how parents handle it, how the suffering of a mother raising a child with autism, her ups and downs, and her communicative actions in raising her child. This research is a qualitative research, the type of research is case study, the social paradigm is social definition, data collection is through observation, interviews, and documentation. Data analysis using the Interactive Miles and Hubermann model with steps including Data Collection, Data reduction, Data display, data conclusion. The results of communicative social action research are needed to overcome children with disabilities, special needs such as people with autism.